2010
DOI: 10.1021/jf903545j
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fusarium Infection on the Phenolics in Emmer and Naked Barley

Abstract: Inoculated or non-inoculated naked barley and emmer cultivars were investigated with regard to their influence on phenolic acid profiles and their arabinoxylan content. Two groups of phenolic compounds were differentiated-methanol-soluble and hydrolyzable covalent-bound phenolic compounds. Chromatographic methods were applied for their analysis. The results showed ferulic acid as the predominant phenol in both total and covalent-bound fractions. The inoculation significantly reduced the ferulic acid content wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 39 publications
(67 reference statements)
2
18
0
Order By: Relevance
“…The reason for this is not clear. In a field experiment, Eggert et al (2010) found that artificial Fusarium inoculation increased the catechin content, reduced the ferulic acid content, but had no effect on the p-coumaric acid content in hulless barley. Probably, the majority of p-coumaric acid has already been used to synthesize flavonoids in black barley which in turn become more resistant to DON accumulation than yellow barley because of the presence of flavonoids (Kumaraswamy et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this is not clear. In a field experiment, Eggert et al (2010) found that artificial Fusarium inoculation increased the catechin content, reduced the ferulic acid content, but had no effect on the p-coumaric acid content in hulless barley. Probably, the majority of p-coumaric acid has already been used to synthesize flavonoids in black barley which in turn become more resistant to DON accumulation than yellow barley because of the presence of flavonoids (Kumaraswamy et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, p-coumaric and ferulic acids have shown significant in vitro inhibition of F. graminearum and F. culmorum isolates (McKeehen et al 1999). Furthermore, p-coumaric acid and other phenylpropanoids were reported from emmer and naked barley cultivars infected with F. graminearum (Eggert et al 2010). In wheat bran p-coumaric, ferulic, and sinapic acids were abundantly present, and the reconstituted phenolic acids of bran inhibited trichothecene biosynthesis in in vitro studies (Boutigny et al 2010).…”
Section: P-coumaric and Sinapic Acidsmentioning
confidence: 99%
“…SF and SC caffeic acid could not be detected in emmer wheat and hence in any sample. It was reported that ferulic acid is incorporated into plant cell wall structures and provides cross-linkages via ester bonds between arabinoxylans, cellulose, lignin, and proteins (Eggert et al, 2010). It was determined that ferulic acid constitutes 74.47% of the total phenolic acid content.…”
Section: Yilmazmentioning
confidence: 99%